Evaluation of the Effect of Complete and Partial Osseointegration in Stress Development at Bone-Implant Interface: A 3D Finite Element Study - Pandey, Bashu Raj; Halwai, Hemant Kumar; Adhikari, Khushbu; Thakur, Amresh (Orthodontic Journal of Nepal, 2016)
Introduction: Mini-implant has been in use as temporary anchorage device in orthodontics. Various factors like length, type of osseointegration, magnitude and direction of force, insertion angle of the mini-implant affect the stress development at the bone and implant interface. Development of undesirable stress at the bone-implant interface can lead to bone defect and failure of the implant. Various opinions regarding the need of osseointegration have been reported. Objective: To study the effect of complete and partial osseointegration on Von Mises stress distribution at the bone-implant interface. Materials & Method: Finite element model of 9mm × 1.5mm mini-implant and bone segment of 1.5mm were constructed to simulate the biomechanical response of the bone to the mini- implant by using CATIA V5-6R 2013 software. Stress developed on implant and bone were analyzed by using ANSYS: 13 2013 version software for both complete and partial level of osseointegration. Result: Maximum Von Mises stress in complete osseointegration was 14.49 Mpa in cortical bone, 0.551 Mpa in cancellous bone and 50.76 Mpa in implant. In partial osseointegration, it was 18.68 Mpa in cortical bone, 1.23 Mpa in cancellous bone and 66.80 Mpa in mini-implant. Conclusion: In partial osseointegration, stress developed was higher but well below the yield strength of respected continuum. So the partial osseointegration is a good compromise between the necessity of reducing mobility of implant and the necessity for easier screw removal. Key words: cancellous bone, cortical bone, Finite element analysis, mini-implant, Von Mises stress